2017
DOI: 10.5530/jyp.2017.9.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arginine on IL-6, IL-17 and TGF-β levels in high-fat diet-induced hypercholesterolemia rat

Abstract: Objective: The aim with the present study was to determine that arginine affect to the level of IL-6, IL-17 and TGF-β in high-fat diet-induced hypercholesterolemia in rats. Material and Methods: Male Wistar rats in eight weeks old (n=35) were divided into five groups, one group as a control (C) were given standard r fed and four groups were given high-fat diet (Hfd) with fats from beef tallow. One group of high-fat diet rats recieved no arginine, three groups were recieved arginine in doses of 100, 200 and 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The mechanism underlying this process involves the regulatory impact of arginine, an amino acid compound, on the production of IL-6 by immune cells, resulting in the attenuation of the IL-6-mediated inflammatory response. Moreover, arginine exhibits immunostimulatory properties, enhancing immune system activity and influencing the immune response to infection and inflammation (Darwin et al, 2017;Martí i Líndez & Reith, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying this process involves the regulatory impact of arginine, an amino acid compound, on the production of IL-6 by immune cells, resulting in the attenuation of the IL-6-mediated inflammatory response. Moreover, arginine exhibits immunostimulatory properties, enhancing immune system activity and influencing the immune response to infection and inflammation (Darwin et al, 2017;Martí i Líndez & Reith, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the level of IL-6 in a HCHF group was higher compared to the control group received standard diet (Table 4). LDL cholesterol activates endothelial cells, macrophages lymphocytes, fibroblast and vascular smooth muscle to secrete Il-6 as soluble mediator of the inflammatory response that will diffuse from sub mucous lining into the vascular lumen, so that the high levels of IL-6 were detected in the blood of high-fat diet rats [36]. Upon swimming exercise we noticed that the concentration of interleukin (IL)-6 increases significantly during exercise in HCHF group compared to healthy rats (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous research indicating that amino acids possess the capacity to influence pain intensity. The underlying mechanism for this effect is the antiinflammatory properties of amino acids, particularly arginine, which helps inhibit the production of proinflammatory cytokines [28,40]. Moreover, amino acids play a role in regulating central nervous system responses that influence neurotransmitters associated with pain perception in the brain.…”
Section: Sendy Mohamad Anugrahmentioning
confidence: 99%
“…According to a literature review, Royal Jelly (RJ) demonstrated the potential to mitigate exerciseinduced muscle damage (EIMD) by reducing the inflammatory response [17,25]. RJ's antiinflammatory properties are believed to contribute to the reduction of TNFa and IL6 [26][27][28]. Furthermore, in the medical field, RJ has been widely utilized for wound healing acceleration and as an anticancer agent [29][30][31] Despite these advantageous antiinflammatory properties, the specific RJ dosage required to reduce MDA levels as a biomarker of oxidative stress and pain intensity after 24 hours of highintensity weight training has not been established.…”
Section: Introductionmentioning
confidence: 99%